Use of essential oils in anxiety disorders: A literature review (Research, Society and Development, 2023)
Introduction: Different people with varied cultures used the medicinal and cosmetic characteristics of plants to control various diseases. Currently, essential oils are gaining prominence for their diverse applications and knowledge about them is being deepened. Objective: To carry out a narrative review on essential oils produced in Brazil that help combat anxiety disorders, in works published from 2020 to 2023. Methodology: This work is a descriptive and exploratory study based on a narrative review of the literature, carrying out research and collecting scientific data organized through the investigation of articles associated with the object of study. Results and discussion: After reading and understanding the work, it became clear the importance of the pharmaceutical professional as a health professional through pharmaceutical care, guiding users of essential oils, clarifying the population regarding the use of herbal medicine in the treatment of anxiety, and ensuring compliance with health standards related to the use of this medicine.